Symmetric Tori connected Torus Network - Faisal, Faiz Al; Rahman, M.M. Hafizur (2009)
A Symmetric Tori connected Torus Network (STTN) is a 2D-torus network of multiple basic modules, in which the basic modules are 2D-torus networks that are hierarchically interconnected for higher-level networks. In this paper, we present the architecture of the STTN, addressing of node, routing of message, and evaluate the static network performance of STTN, TTN, TESH, mesh, and torus networks. It is shown that the STTN possesses several attractive features, including constant degree, small diameter, low cost, small average distance, moderate bisection width, and high fault tolerant performance than that of other conventional and hierarchical interconnection networks.